Impact of contrast echocardiography on accurate discrimination of specific degree of left ventricular systolic dysfunction and comparison with cardiac magnetic resonance imaging. Issue 11 (30th October 2018) - Alherbish, Aws; Becher, Harald; Alemayehu, Wendimagegn; Paterson, D. Ian; Butler, Craig R.; Anderson, Todd J.; Ezekowitz, Justin A.; Shanks, Miriam; ,
Abstract : Aim: Limited data exist on the impact of contrast‐enhanced echocardiography on treatment decisions in heart failure patients that require specific left ventricular ejection fraction (LVEF) criteria. This study assessed accuracy of contrast‐enhanced echocardiography in identifying patients with LVEF >35% vs ≤35% with cardiac magnetic resonance (CMR) used as reference method. Methods and results: Fifty‐five patients from prospective Alberta HEART cohort with LVEF ≤50% on CMR were included. All patients had echocardiography performed within 2 weeks of CMR. Contrast agent was used when ≥2 contiguous LV endocardial segments were poorly visualized on echocardiography. LVEF was computed by Simpson's biplane method using non‐contrast echocardiography and contrast‐enhanced echocardiography and by outlining the endocardial contours in short‐axis cine CMR images. Strong agreement in LV volumes and LVEF was seen between CMR and echocardiography with and without contrast (intra‐class correlation coefficients >0.8) with less underestimation of LV volumes by contrast‐enhanced echocardiography. Good agreement in LVEF ≤35% vs >35% was seen between CMR and non‐contrast echocardiography with optimal images ( κ 0.862) and contrast echocardiography ( κ 0.769) while it was moderate for non‐contrast echocardiography with suboptimal images ( κ 0.491). The use of LV contrast in patients with suboptimal images (n = 39) resulted in correctly upgrading LVEF from ≤35% to >35% in 5 (13%) patients and downgrading LVEF from >35% to ≤35% in 2 (5%) patients using CMR as reference. Conclusions: Contrast‐enhanced echocardiography in heart failure patients with suboptimal images helps to more accurately assess eligibility for specific therapies and avoid need for further testing, therefore should be considered routine part of echocardiographic assessment.